H.R. 1508, A Bill, To Amend The Internal Revenue Code Of 1954 To Increase To 32 Cents Per Pack The Federal Excise Tax On Cigarettes (Tufts Archival Research Center, 2007)
Bill to amend the Internal Revenue Code of 1954 to increase to 32 cents per pack the federal excise tax on cigarettes. Provides that the revenues from such tax shall be divided among the general fund, the Federal Hospital Insurance Trust Fund under the Social Security Act, and research on tobacco-related diseases.